Determinants of Household COVID-19 Cases: The Role of Personal Hygiene, Environment, Individual Characteristics, and Mobility in Gading Village, Surabaya - Kusnadi, Bunga Devita Putri; Sulistyorini, Lilis (Baiman Bauntung Batuah Center, 2025)
COVID-19 is a disease caused by the SARS-CoV-2 virus and attacks the human respiratory system. As of 2021, the virus has spread to 226 countries, including Indonesia. East Java Province has the fourth-highest number of cases in Indonesia, while Surabaya City has the highest number of cases in East Java. This study aims to analyze the relationship between Personal hygiene, environmental conditions, individual characteristics, and mobility with COVID-19 cases in households in Gading Village, Tambaksari District, Surabaya City. This study is an observational analytic study using a case-by-case approach. Cross-sectional. The study was conducted in Gading Village, Tambaksari District, Surabaya City, from September 2022 to December 2022. The sample consisted of 85 households selected through a simple random sampling. Data collection was carried out using questionnaires and observations. The results were tested using the chi-squared and Fisher's Exact Test with a significance level of 0.05. The results of the study showed that home ventilation (p=0.036) and residential density (p=0.04) had a significant relationship with COVID-19 cases in households. Meanwhile, no significant association was found with the incidence of COVID-19 in the variables of age (p=0.603), gender (p=0.405), comorbidities (p=0.924), handwashing behavior with soap (p=1.000), mask use (p=0.294), social distancing behavior (p=0.341), environmental cleanliness (p=0.414), and work/learning systems of household respondents (p=0.751). The conclusion shows that home ventilation factors and residential density have a significant relationship with cases of COVID-19 transmission. Therefore, efforts to prevent COVID-19 transmission in the household environment need to focus on improving home ventilation and reducing residential density. In addition, education regarding other risk factors is still necessary to increase public awareness in maintaining overall health and environmental cleanliness.